Systematic Review dan Meta-Analisis: Kadar Hemoglobin dan Risiko Atonia Uteri di Indonesia - Khoidatun Maufiroh; Astika Gita Ningrum; Bambang Purmwanto (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
The incidence of primary postpartum hemorrhage in Indonesia is 70% caused by uterine atony. Anemia is one of the causes of uterine atony, the incidence of anemia in pregnant women in Indonesia in 2013 was 37.1% and there was an increase in 2018 to 48.9%. This study aims to analyze the relationship between low maternal hemoglobin levels and the incidence of uterine atony. This research is secondary research using a systematic study with a time limit of articles taken from 2015-to 2019. Article searches were systematically reviewed through ScienceDirect, Google Scholar, and SINTA databases. The final results were 10 articles according to the inclusion and exclusion criteria. Calculation of results using Meta-analysis with the help of Comprehensive Meta-Analysis (CMA) software. Comparing the odds ratio and confidence interval of Hb levels compared to the incidence of uterine atony. The results showed OR 4,966 (95% CI 3,842 – 6,418) and a p-value <0.001, so there was a relationship between hemoglobin levels of pregnant women 11gr/dL with the incidence of uterine atony. In the results of the heterogeneity test of the sample, the I-Squared result is 62.592%, which indicates the I-squared heterogeneity value is > 50% so the sample used is heterogeneous. The results showed that there was a relationship between low hemoglobin levels and the incidence of uterine atony. Regular pregnancy check-ups are needed so that pregnant women can detect hemoglobin levels as early as an indicator of anemia in pregnancy so that prevention and treatment of anemia can be carried out properly. Keywords: Hemoglobin level of pregnant women, anemia, uterine atony